Opportunistic spectrum access method for cognitive radio sensor network of typical deployment strategies - Wen-xiang LI; Ya-jie MA; Peng KE (Tongxin xuebao)
Explored the opportunistic spectrum access method for cognitive radio sensor networks with regular topology patterns and coverage patterns.The method includes an economic spectrum-and-timeslot-allocation scheme,a sensing-results-reporting scheme and a cooperative spectrum-sensing scheme.A model was proposed for analyzing the blocking and dropping probability for secondary users,the effective reception bandwidth and transmission delay.Numerical analysis shows that Triangle yields the optimal cooperative sensing performance,and square yields the optimal reception bandwidth.In case of complete coverage,Square and triangle lead to less transmission delay,and in case of multiple coverage,square leads to the least transmission delay.The false alarm probability of single node has little impact on transmission delay,and Primary User’s activity may affect delay noticeably.On the other hand,larger ratio of transmission timeslot to sensing timeslot helps to decrease delay.